2021
DOI: 10.1259/bjr.20200997
|View full text |Cite
|
Sign up to set email alerts
|

CT findings of acute radiation-induced pneumonitis in breast cancer

Abstract: Objectives: To evaluate the computed tomography (CT) findings of acute radiation pneumonitis (RP) in breast cancer patients undergoing postoperative radiotherapy, and to analyze clinico-dosimetric factors associated with acute RP. Methods: Between 2015 and 2017, 61 patients with breast cancer who underwent follow-up chest CT at 3 months after radiotherapy were analyzed. The degree of acute RP on CT was evaluated by the change of extent and scoring system (grade 0, no RP; Grade 1, ground-glass opacities (GGOs);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…As expected, the risk of RP increased significantly when lymph node irradiation was indicated, expressed as symptomatic RP incidences increased by a factor of 1.6 (PCN inclusion) and 2.6 (PCN + IMN inclusion). Due to the applied moderately higher dose concepts used during the study, the observed overall RP incidence was higher than reported for comparable patient cohorts, especially as IMRT/VMAT is commonly performed nowadays [ 38 42 ]. However, in our cohort, all 40 patients with diagnosed RP ≤ grade II exhibited moderate symptoms, and all of them recovered completely within a median time of 9 months (range 1 to 24 months).…”
Section: Discussionmentioning
confidence: 95%
“…As expected, the risk of RP increased significantly when lymph node irradiation was indicated, expressed as symptomatic RP incidences increased by a factor of 1.6 (PCN inclusion) and 2.6 (PCN + IMN inclusion). Due to the applied moderately higher dose concepts used during the study, the observed overall RP incidence was higher than reported for comparable patient cohorts, especially as IMRT/VMAT is commonly performed nowadays [ 38 42 ]. However, in our cohort, all 40 patients with diagnosed RP ≤ grade II exhibited moderate symptoms, and all of them recovered completely within a median time of 9 months (range 1 to 24 months).…”
Section: Discussionmentioning
confidence: 95%